Determination of free glycerin and mono-, di-, triglycerides in palm-based biodiesel using fast gas chromatography / Pua Swee Ping - Pua, Swee Ping (2014)

(untitled)
As the tremendous growth of biodiesel industry, demand of fast analysis turnaround time becomes essential to sustain the drastic increase of samples quantity and to deliver the result on time. A fast gas chromatography (GC) method was developed using a shorter metal column to determine free glycerin and total glycerin, as well as mono-, di-, and triglyceride content in biodiesel. More than two times reduction of analysis time (16 minutes) was achieved by using this fast GC method without sacrificing the peaks resolution. Method validation results show good linearity (r2 > 0.95) and repeatability (RSD < 8%) with acceptable limit of quantification. In addition, the calibration modules proposed in this method covers the quantification of biodiesel derived from wide range of fatty acids carbon chain, including lauric based methyl esters. This research covers the various parameters used in developing the fast GC method to analyse palm kernel and palm stearin based biodiesel.